Poverty Analysis in Bunta II Village, Bunta District, Banggai Regency - Andi Herman Jaya; Nasrianti Nasrianti; Aris Muhammad (Institute of Computer Science (IOCS), 2021)
This study aims to find out the level of poverty, the level of poverty depth, the severity of poverty and the characteristics of poverty in Bunta II Village of Bunta District of Banggai Regency. The type of research used is descriptive using primary and secondary data. Data collection techniques are carried out using observation, interview, and questionnaire techniques. The data analysis tools used are the Head Count Index (HCI), Poverty Gap Index (PGI) and Poverty Severity Index (P2). The results of the study showed that based on the results of the Head Count Index (HCI) analysis, it was known that the poverty rate in Bunta II Village of Bunta District of Banggai Regency amounted to 0.650 or 65.0 percent, Based on the poverty gap index (PGI) analysis.